Pengaruh Kepribadian dalam Meningkatkan Loyalitas Merek Disney+Hotstar di Indonesia - Odelia, Franciska; Madeline, Victoria; Joseph Wibowo, Alexander Ibnu; Yudianto, Bernadinus Realino (Kajian Branding Indonesia, 2024)
This study analyzes the influence of personality on consumer benefits, perceived quality, and brand loyalty of Disney+ Hotstar in Indonesia. In addition, this study also analyzes the effect of consumer benefits and perceived quality on Disney+ Hotstar’s brand loyalty in Indonesia. This research methodology uses a quantitative methodology where researchers collected data from 388 respondents and processed using the statistical programs SPSS 27 and AMOS 26. This research proves that “excitement” personality influences the "superhero" and "fiction and drama" genres. The "excitement" personality influences the "superhero" genre. The "superhero" genre influences brand loyalty.. The personalities of "excitement", "modernity", and "sincerity" influence perceived quality. Perceived quality is stated to influence brand loyalty. Personality is stated not to affect brand loyalty. This research proves the variable correlation of the antecedent variables of the formation of Disney+ Hotstar brand loyalty in Indonesia.